Genetic Engineering - A Glimpse of Techniques and Applications 2020
DOI: 10.5772/intechopen.84782
|View full text |Cite
|
Sign up to set email alerts
|

Genome Engineering for Xenotransplantation

Abstract: Xenotransplantation, the transfer of cells, tissues or organs between species, has the potential to overcome the critical need for organs to treat patients. One major barrier in the widespread application of xenotransplantation in the clinic is the overwhelming rejection response that occurs when non-human organs encounter the human immune system. Recent progress in developing new and better genome engineering tools now allows the genetic engineering of genes and pathways in non-human animals to overcome the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…According to the Organ Procurement and Transplantation Network, there are presently over 110,000 patients on the organ transplant waiting list, yet the number of organs available through donation has remained relatively constant, and even a massive increase in organ donation would not guarantee that a compatible organ would be available when and where needed for a patient (Stevens, 2019). Scientific studies found that xenotransplantation may be a viable approach (Hryhorowicz et al, 2017), in which it is a technique that includes the transplantation, implantation, or infusion of living cells, tissues, or organs from non-human animal sources into a human recipient (Krishnasamy, 2007).…”
Section: H Umanized Pig Organ Productionmentioning
confidence: 99%
“…According to the Organ Procurement and Transplantation Network, there are presently over 110,000 patients on the organ transplant waiting list, yet the number of organs available through donation has remained relatively constant, and even a massive increase in organ donation would not guarantee that a compatible organ would be available when and where needed for a patient (Stevens, 2019). Scientific studies found that xenotransplantation may be a viable approach (Hryhorowicz et al, 2017), in which it is a technique that includes the transplantation, implantation, or infusion of living cells, tissues, or organs from non-human animal sources into a human recipient (Krishnasamy, 2007).…”
Section: H Umanized Pig Organ Productionmentioning
confidence: 99%
“…In the 1960s, experiments by various teams showed that while it was technically possible to transplant animal organs into humans, there were still too many clinical challenges at that time for the approach to be viable. Significant advancements have been made in recent years in understanding the molecular mechanisms of xeno-rejection responses (Cooper, 2012;Stevens, 2020). These have been made possible due to the advances in synthetic genomics and fundamental genomics, which while essential are only a small part of the overall transplantation process.…”
Section: Emerging Technologies That Could Revolutionize Biology: Adva...mentioning
confidence: 99%
“…The pig genome was sequenced to very high coverage Review to ensure accuracy. The accurate genome allowed for highly specific targeted gene knockouts and for the insertion of cassettes of human genes in specific sites without disrupting genome functions (Stevens, 2020).…”
Section: Emerging Technologies That Could Revolutionize Biology: Adva...mentioning
confidence: 99%
“…Furthermore, with access to xenotransplantation, a commonly developing animal donor which is pig, allows the elderly patients to be able to receive the organ that is compatible to them since the donated organ from pig will solve the age limits the transplantation [34]. A further advantage of xenotransplantation is that the procedure can be pre-scheduled which will allow patients to have pre-treatment of receiving immunosuppressive agents to prevent the rejection after the surgery [4,41,42]. Apart from medical terms, xenotransplantation will also produce two significant benefits to patients and donors [43].…”
Section: E Advantages and Disadvantagesmentioning
confidence: 99%